Euphorbiaceae novae vel criticae colombianae, IV Euphorbiaceae novae vel criticae colombianae, IV - Croizat León (Caldasia)
<span style="font-size: 12.0pt; font-family: ";Arial";,";sans-serif";; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: ES; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Croton Linnaeus / Croton palanostigma / Croton cearensis / Croton huitotorum / Croton Killipianus / Croton Smithianus / Croton chocoanus / Croton sibundoyensis / Croton boavitanus / Croton Purdiei / Croton polycarpus / Croton magdalenensis / Croton Mutisianus / Croton ater / Croton Lechleri / Croton gossypiifolius / Croton hibiscifolius <span style="font-size: 12.0pt; font-family: ";Arial";,";sans-serif";; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: ES; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Croton Linnaeus / Croton palanostigma / Croton cearensis / Croton huitotorum / Croton Killipianus / Croton Smithianus / Croton chocoanus / Croton sibundoyensis / Croton boavitanus / Croton Purdiei / Croton polycarpus / Croton magdalenensis / Croton Mutisianus / Croton ater / Croton Lechleri / Croton gossypiifolius / Croton hibiscifolius.